RELASI AGAMA DAN SAINS DALAM ISLAM (Pemetaan Konteks Awal dan Varian Pemikiran Sains Islam) - Ach. Maimun (Muslim Heritage, 2020)
AbstractVarious models of ideas on the relationship between religion (Islam) and science reappear recently when some UIN (Universitas Islam Negeri/State Islamic University) have been established. The thoughts of the relationship between Islam and science not only turn into integrative concept, but also seem to be more various. Apparently, the root of the variations could be retraced through previous Islamic thoughts in the history of Islam. There has been interconnected practical problem within historical context i.e. Islam had a military defeat against the West and the consciousness of being backward in sciences and technology. Furthermore, it then brings “a syndrome of catching up” which is translated as endeavours based on the relational thoughts of Islam and science. The preliminary endeavours are emphasized on practical and artificial aspect as the colonialized country. However, the next development shows that a more comprehensive endeavour appears in the form of philosophical thoughts and followed by the way how to implement them practically. In this case, there are three school of thoughts: instrumentalist, restorationist and constructionist. The last school creates four trends: bucailist, fundamentalist, adaptationist and metaphysic, while the last trendcreates three more streams: philosophic-sufistic, traditionalist and accommodationist. Each thought has its specificities and similarities. The development of all variants is influenced by different experiences, knowledges and perspectives belong to each thinker, although every thinker probably has the same socio-historical background. All of them are the valuable richness that have been appreciated by theconceptualisers of UIN. AbstrakBerbagai model gagasan tentang relasi agama (Islam) dan sains mengemuka kembali dengan lahirnya berbagai Universitas Islam Negeri (UIN) di Indonesia. Gagasan relasi Islam dan sains terarah pada konsep integrasi yang juga memperlihatkan keragamannya. Rupanya, berbagai konsep yang beragam tersebut telah memiliki cikal bakalnya pada pemikiran Islam sebelumnya dalam sejarah Islam. Hal itu tak bisa dilepaskan dari konteks historis berupa berupa problem praktis, yaitu kekalahan militer Islam dari Barat dan kesadaran akan ketertinggalan karena ketertinggalan di bidang sains dan teknologi. Inilah yang melahirkan “sindrom pengejaran ketertinggalan” (catching up syndrom) yang diterjemahkan dalam upaya-upaya yang didasarkan pada pemikiran tentang relasi Islam dan sains. Upaya-upaya awal tersebut menekankan pada aspek kepraktisan dan artifisial sebagai negara terjajah. Hanya dalam perkembangannya, muncul upaya-upaya yang lebih mendalam dalam bentuk pemikiran filosofis dan dilanjutkan dengan penerapan praktisnya. Dalam hal ini muncul tiga madzhab pemikiran: instrumentalis, restorasionis dan konstruksionis. Madzhab terakhir terbagi menjadi empat aliran: bucailis, fundamentalis, adaptasionis dan metafisik. Aliran terakhir terbagi lagi menjadi tiga kubu: filosofis-sufistik, tradisionalis dan akomodasionis. Masing-masing pemikiran memiliki spesifikasinya sendiri-sendiri di samping ada kesamaan-kesamaannya. Walaupun dilatari oleh konteks sosial historis yang hampir sama, perbedaan gagasan itu muncul disebabkan oleh pengalaman, pengetahuan dan perspektif yang berbeda pada masing-masing pemikir. Semuanya adalah kekayaan khazanah yang telah diapresiasi oleh para konseptor UIN di Indonesia.